Survival of dental implants in irradiated head and neck cancer patients compared to non-irradiated patients: An umbrella review - Maria Cândida Dourado Pacheco; Alexandre Henrique dos Reis Prado; Danilo Viegas da Costa; Lara Cancella de Arantes; Caio Fernando Teixeira Portela; Tarcísio Passos Ribeiro Campos; Arno Heeren de Oliveira (PLoS ONE, 2025)
Background: There is an increasing demand for oral rehabilitation in patients undergoing irradiation for head and neck cancer treatment. Although radiotherapy appears to adversely affect implanted oral rehabilitation, the evidence provided by previous systematic reviews in the field remains controversial. Thus, this umbrella review aimed to evaluate the survival of dental implants installed before and/or after radiotherapy in patients with head and neck cancer compared to those not irradiated. Methods: A comprehensive search of electronic databases was performed in the PubMed, Cochrane Library, Embase, Web of Science, and Google Scholar databases, including manual searches, from inception to February, 2024, with no language or date restrictions. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines were followed. Survival percentage of dental implants was the primary outcome. A Measurement Tool to Assess systematic Reviews (AMSTAR) 2 was used as a critical appraisal tool for the included studies. The protocol for this review has been registered with PROSPERO (CRD42023406059). Results: Of the 1,811 articles screened, 11 articles that evaluated 73,674 implants were included. Quantitative analyses showed 2,674 failures out of 14,471 implants installed in irradiated bone and 1,825 failures out of 34,092 implants in non-irradiated bone. The survival rate was 81.52% for irradiated implants and 94.64% for non-irradiated implants. A significant difference in survival in favor of implants in non-irradiated bone is supported by 11 meta-analyses. The included systematic reviews showed critically low methodological quality. Conclusions: Although the included studies had low methodological quality, the findings indicate a higher failure rate of implants in irradiated patients. Further well-designed clinical studies are warranted.